PROSPEK PENGEMBANGAN ES GABUS BUAH DAN SAYUR, CITA RASA JADUL KAYA VITAMIN - Zenita Mulya Astuti; Anindya Abdi Nusara; Cisya Vidya Anggraini; Viska Wandhira Wimarnaya; Nurul Fadhila; Bara Yudhistira (Jurnal Kewirausahaan dan Bisnis, 2019)
In this modern era, many snacks that are not safe for health are sold to children and they like them very much. This problem is very serious to note because it is related to children's health. To overcome or reduce this problem, created an innovation of healthy snacks that are rich in vitamins, namely Ice Cork Fruit and Vegetables from various types of vegetables such as carrots, mustard greens, and purple yams. Ice Cork Vegetables are made with the aim of increasing interest in vegetable consumption in children. The target is to attract the interest of children to eat delicious snacks, safe and healthy through EGAYUR (VEGE ICE). Because in general children like to eat snacks that are tasty and refreshing, cork ice for example. The method for realizing this idea is to create an entrepreneurial business program that produces EGAYUR (VEGE ICE). The first thing to do is to make an SOP for making EGAYUR (VEGE ICE). Then do the trial making of EGAYUR (VEGE ICE) products, do research on the taste variants that consumers like, then do the production process. In one production it will produce 75 products, which are done once a week for 4 months. So that the total production for one month is 75 products.Keywords : ice cork, vegetables, vitamins